Students’ Motivation in Learning English Using Edmodo - Muhammad Ichwan Arif; Rizki Ramadhan (STKIP Al Hikmah Surabaya, 2020)
The purpose of this research was to describe students’ motivation toward the implementation of Edmodo in learning English. The subjects was twenty students in 7B class of SMP Lab School UNESA. To specify the data, the researcher classified them by considering their background knowledge, which had been chosen by the teacher, aimed for conducting an interview. There were six students consisted of two students in high level, two students in middle and two students in low level. Descriptive qualitative was used as the design of this research. For collecting the data, this research used classroom observations, questionnaires and interview, and they were analysed by using Miles and Huberman’s Theory. Finally, it was found that most of subjects were motivated when the teacher used Edmodo in learning English. Specifically, the students in high-middle level were also motivated in learning English, but for those in low-level, a subject has low level of challenge, and another student was not motivated in using Edmodo. It means that the use of Edmodo should be paid attention by looking at the students’ ability when applying the media in learning English. For the aspect of Edmodo that determine students’ motivation, the findings were explained that most of the students preferred to use Edmodo because there was no need for them to do hand-writing. They also felt interested in learning variation. Those variations are: the application, the audio and the picture. Those variations helped the students understand the lesson easily and could develop their motivation in learning English.